2021
DOI: 10.3390/ijms222111479
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of SlCML39, a Tomato Calmodulin-like Gene, and Its Negative Role in High Temperature Tolerance of Arabidopsis thaliana during Germination and Seedling Growth

Abstract: Calmodulin-like (CML) proteins are primary calcium sensors and function in plant growth and response to stress stimuli. However, so far, the function of plant CML proteins, including tomato, is still unclear. Previously, it was found that a tomato (Solanum lycopersicum) CML, here named SlCML39, was significantly induced by high temperature (HT) at transcription level, but its biological function is scarce. In this study, the characteristics of SlCML39 and its role in HT tolerance were studied. SlCML39 encodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…In tomato, SlCML37 interacts with proteasome maturation factor SlUMP1 and plays a role in fruit chilling stress tolerance (Tang et al, 2021). SlCML39 acts negatively in high temperature tolerance possibly through ABA signaling pathway (Ding et al, 2021). Overexpression of ShCML44 enhances tolerance to cold, drought and salinity stress by higher antioxidant enzymes activity, less membrane damage, better gas exchange and plant water relations in Solanum habrochaites (Munir et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In tomato, SlCML37 interacts with proteasome maturation factor SlUMP1 and plays a role in fruit chilling stress tolerance (Tang et al, 2021). SlCML39 acts negatively in high temperature tolerance possibly through ABA signaling pathway (Ding et al, 2021). Overexpression of ShCML44 enhances tolerance to cold, drought and salinity stress by higher antioxidant enzymes activity, less membrane damage, better gas exchange and plant water relations in Solanum habrochaites (Munir et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…CaMRLK plays vital roles in protein phosphorylation in eukaryotes, related to high temperature, cold and drought stress in plants (Ding et al, 2021). In addition, we found more complex adaptation in high elevations (>3000 m) including five kinds of genes responsible for the regulation of alpine evolution (Table S3).…”
Section: Continuous Genetic Adaptation In Situ Under Climate Changementioning
confidence: 83%
“…RH38 is a member of the DEAD‐box family primarily involved in abiotic stress, and a study found RH38 having upregulated expression under cold stress but more sensitive to thermal stress in Arabidopsis thaliana (Chen & Peng, 2016). CaMRLK plays vital roles in protein phosphorylation in eukaryotes, related to high temperature, cold and drought stress in plants (Ding et al, 2021). In addition, we found more complex adaptation in high elevations (>3000 m) including five kinds of genes responsible for the regulation of alpine evolution (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…The pronounced induction of OsMSR2 expression by HS suggests its involvement in thermotolerance. Furthermore, SlCML39 , a CML gene from tomato, was found to have a negative impact on thermotolerance during germination and seedling growth in A. thaliana [ 94 ]. SlCML39 is expressed in various tissues in tomato plants, including leaves, stems, roots, flowers, and fruits.…”
Section: Ca 2+ -Binding Protein Involvement In The...mentioning
confidence: 99%